Мотивація персоналу як один з факторів підвищення ефективності роботи підприємства - Яковенко, В. Г.; Куделя, В. І. (НТУ "ХПІ", 2014)
Розглянуто основні фактори, що визначають вплив мотивації персоналу на підвищення продуктивності праці та ефективності роботи підприємства. Представлено основні грошові та не грошові фактори мотивації праці.

Major factors which define influence of motivation of the personnel on increase of labor productivity and overall performance of the enterprise are considered. The main are presented monetary and not monetary factors of motivation of work.
Motivation of the personnel as one of factors of increase of overall performance of the enterprise
Keywords: ринкова економіка; механізми господарювання; мотивація праці; управління персоналом; методи мотивації; motivation of work; human resource management; motivation of the personnel